2000
DOI: 10.1046/j.1365-2915.2000.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that deltamethrin‐impregnated collars protect domestic dogs from sandfly bites

Abstract: In many foci of zoonotic visceral leishmaniasis (ZVL), domestic dogs are important reservoir hosts of the causative Leishmania parasites transmitted by phlebotomine sandflies (Diptera: Psychodidae). We tested the protective value of impregnated dog collars (20 g plastic containing deltamethrin 800 mg ai) against Phlebotomus papatasi (Scopoli) sandflies in Iran. For each assay, the dog was sedated and caged in a net with 70-100 wild-caught sandflies overnight (23.30-06.30 hours). Dogs wearing the collars were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 9 publications
4
30
1
Order By: Relevance
“…His study was carried out over 26 weeks. Recently, Halbig et al (2000) reported on a study in Iran using the same deltamethrin collars and wild-caught P. papatasi confined with large guard dogs. They tested the anti-feeding and killing effect before attachment and after the collars had been on the dogs for eight days.…”
Section: Resultsmentioning
confidence: 99%
“…His study was carried out over 26 weeks. Recently, Halbig et al (2000) reported on a study in Iran using the same deltamethrin collars and wild-caught P. papatasi confined with large guard dogs. They tested the anti-feeding and killing effect before attachment and after the collars had been on the dogs for eight days.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of the results of our trial with those of similar studies with DM collars (25)(26)(27) are difficult because of differences in experimental protocols. For example, we used wild-caught Lu.…”
Section: Emerging Infectious Diseasesmentioning
confidence: 90%
“…Both trials demonstrate that, when collars are used, the effects persist much longer than when dogs are dipped in DM. The potentially wide applicability of DM collars for protecting dogs against sand flies has since been demonstrated by experimental trials with P. papatasi in Iran (27).…”
Section: Emerging Infectious Diseasesmentioning
confidence: 99%
“…Also, according to Halbig et al [42], the efficacy of the collar is around 80%. Therefore, we considered that a proportion ε c of those dogs using collar is protected.T19xd˙t=Bt+uc+ζcxdCt+rdldt+γdzdtθd+bdadmds3txdtld˙t=uc+ζcldCt+bdadmds3txdt…”
Section: Modeling the Dynamic Of Control Strategiesmentioning
confidence: 99%